6
$\begingroup$

$$f(x)+xf(-x)=x-2$$ what is $f(x$)? I try to solve this problem, but I don't know how to remove $f(-x)$ or converting it to $f(x)$.

$\endgroup$
14
$\begingroup$

Replacing $x$ by $-x$, we have $$f(-x) - xf(x) = -x - 2$$

Substituting back into the original equation $$f(x) + x(xf(x) -x - 2) = x- 2$$ $$(1+x^2)f(x) = x^2 +3x - 2$$ $$f(x) = \frac{x^2 +3x - 2}{1+x^2}$$

$\endgroup$
6
$\begingroup$

we have $$f(x)+xf(-x)=x-2$$ setting $x=-x$ we obtain $$f(-x)-xf(x)=-x-2$$ thus we have $$f(x)+x(-x-2+xf(x))=x-2$$ and we get after eliminating $f(x)$ $$f(x)=\frac{x^2+3x-2}{1+x^2}$$

$\endgroup$
  • $\begingroup$ "Setting $x=-x$", we obtain $x=0$ and $f(0)+0f(0)=0-2$. Perhaps you meant "replacing $x$ by $-x$" or "setting $y=-x$". $\endgroup$ – JiK Nov 30 '14 at 11:08
3
$\begingroup$

After solving such task as in the above answers, you should always test it: you put $\frac{x^2 +3x - 2}{1+x^2}$ instead of $f(x)$ into the given equation:

$$\frac{x^2 +3x - 2}{1+x^2} + x\frac{x^2 -3x - 2}{1+x^2} =$$ $$= \frac{x^2 + 3x - 2 +x^3 - 3x^2 - 2x}{1+x^2} =$$ $$= \frac{x^3 - 2x^2 + x - 2}{1+x^2} =$$ $$= \frac{(x-2) (x^2+1)}{1+x^2} = x-2$$

I forgot to do it once on a maths competition and it cost me a point.

$\endgroup$
  • $\begingroup$ Why does one needs to test? You should be confident about your calculations. Else you will just loose time in exams. $\endgroup$ – Babai Nov 29 '14 at 13:55
  • $\begingroup$ @Susobhan,I don't know why,but contests seem to cut points for not checking the validity of solutions of functional equations.Maybe this is because the solution we get may not be a function,I am not sure. $\endgroup$ – rah4927 Nov 29 '14 at 15:27
  • 8
    $\begingroup$ Testing is necessary to show that you didn't start with a contradiction: anything logically follows from a contradiction, and the other answers have not shown that the starting point was not a contradiction. $\endgroup$ – hvd Nov 29 '14 at 20:30
  • $\begingroup$ Or you could see it this way: other answers proved: if <given conditions> then f=... So an implication, not equivalence. So you need to proove the implication the other way, too: if f=... then <given conditions>. The conditions are not necessarily contradictory when it doesn't work. Such tasks are often set as "Find all f that satisfy ...". You might conclude that f belongs to set F, but do all functions from set F satisfy ...? $\endgroup$ – Heimdall Nov 30 '14 at 23:46

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.